THE INFLUENCE DENTAL HEALTH EDUCATION ON BEHAVIOR AND DEBRIS INDEX OF STUDENTS - Reca; Mufizarni (Jurnal Ilmiah Keperawatan, 2024)
Dental caries is an infectious disease resulting from the demineralization of enamel and dentin, closely linked to the consumption of cariogenic foods. Typically, children entering school age face a heightened risk of caries due to their inclination toward snacking on sweet foods and drinks. The implementation of Dental Health Education (DHE) plays a crucial role in enhancing students' comprehension of dental and oral health. Specifically, educating children on proper teeth-brushing techniques should include practical examples and applicable methods. This study aims to assess the impact of dental health education on the behavior and fecal index of students at SDN Mesjid Lheu in Aceh Besar District. Employing a quasi-experimental design, the research follows a control group equivalent to pre-test and post-test. The total population of 60 children was divided into two groups: the intervention group and the control group. Quantitative data analysis involved the paired sample t-test and the independent t-test. Significant differences were observed in the mean values of knowledge, attitudes, and actions, as well as the OHI-S scores immediately after and one month following the intervention between the treatment group and the control group (p<0.05). To reinforce children's dental health habits at home, it is advisable to involve parents in dental health education programs, as their information and resources are integral to providing support and monitoring.